2010
DOI: 10.1007/s10528-009-9328-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the g.–723G→T Polymorphism in the Bovine Myogenic Factor 5 (Myf5) Gene Promoter Region on Gene Transcript Level in the Longissimus Dorsi Muscle and on Meat Traits of Polish Holstein-Friesian Cattle

Abstract: Myogenic factor 5 (Myf5), a product of the Myf5 gene, belongs to the MRF family of basic helix-loop-helix transcription factors that regulate myogenesis. Their roles in muscle growth and development make their genes candidates for molecular markers of meat production in livestock, but nucleotide sequence polymorphism has not been thoroughly studied in MRF genes. We detected four single nucleotide polymorphisms (SNPs) within exon 1 of the Myf5 gene, encoding the NH-terminal transactivation domain of the Myf5 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Previously we showed that in 12-month-old HF bulls the g.-723G>T transition located within the promoter region of the MYF5 gene influenced the gene expression in the LD muscle and was associated with sirloin weight and fat weight in sirloin in carcasses of HF cattle (Robakowska-Hyzorek et al 2010).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previously we showed that in 12-month-old HF bulls the g.-723G>T transition located within the promoter region of the MYF5 gene influenced the gene expression in the LD muscle and was associated with sirloin weight and fat weight in sirloin in carcasses of HF cattle (Robakowska-Hyzorek et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…TATA box binding protein (TBP) gene was chosen for normalization of expression of MYF6 and MYF5 genes as the most stably expressed in bovine muscle (Robakowska et al 2010). The real-time polymerase chain reactions were performed using the following mix: 0.8 µl of 10µM forward and reverse primers; the Power SYBR ® Green PCR Master Mix (added according to the manufacturer's protocol); 500 ng cDNA used as a template.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its upstream region is highly conserved [27]. Robakowska-Hyzorek et al [28] found that mutation g.-723G ? T affected sirloin weight and fat mass of Polish Holstein-Friesian cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, polymorphisms in the porcine MyF-5 gene and its relationship with different meat traits in different pig lines and breeds have also been reported (Venza et al, 2009;Kunhareang et al, 2009;Robakowska-Hyzorek et al, 2010).…”
Section: Snp Marker Associationsmentioning
confidence: 98%